2016
DOI: 10.1139/cjps-2014-0425
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen source and placement effects on stand density, pasmo severity, seed yield, and quality of no-till flax

Abstract: Field studies were conducted at two locations in western Manitoba over three years to evaluate the impact of rate, source, and placement of nitrogen (N) fertilizer on seedling emergence, disease severity, crop yield, and seed quality of flax (Linum usitatissimum L.). Urea, urea ammonium nitrate (UAN), and ammonium nitrate (AN) fertilizers were applied at 0, 30, 60, and 90 g N ha −1 , pre-plant banded or side-banded 2.5 m to the side and 2.5 m below the seed-row, using a hoe-type opener with 20 m row spacing. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
(33 reference statements)
5
10
0
Order By: Relevance
“…The increase in flax straw yield and its attributes due to AN followed by AS form might be attributed to its increased the availability of nutrients and efficiency improved uptake, thus increased growth rate resulted in raising plant height and straw yield plant -1 which led to increasing straw yield fed -1 , also the increase in straw yield might be attributed to the main role of N in stimulating and raising plant growth and productivity, therefore increased straw yield. Under different soil type conditions, the same trend was found by Soethe et al (2013) and Grant et al (2016) Figure 1 illustrated that a significant effect due to the interaction between flax cultivars and nitrogen sources for stem diameter in the 1 st growing season and straw yield plant -1 and straw yield fed -1 in the 2 nd one was found. It is clearly observed that the highest values for most studied characteristics of straw yield and its components were obtained from Sakha-1 fertilized by ammonium nitrate or ammonium sulfate.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The increase in flax straw yield and its attributes due to AN followed by AS form might be attributed to its increased the availability of nutrients and efficiency improved uptake, thus increased growth rate resulted in raising plant height and straw yield plant -1 which led to increasing straw yield fed -1 , also the increase in straw yield might be attributed to the main role of N in stimulating and raising plant growth and productivity, therefore increased straw yield. Under different soil type conditions, the same trend was found by Soethe et al (2013) and Grant et al (2016) Figure 1 illustrated that a significant effect due to the interaction between flax cultivars and nitrogen sources for stem diameter in the 1 st growing season and straw yield plant -1 and straw yield fed -1 in the 2 nd one was found. It is clearly observed that the highest values for most studied characteristics of straw yield and its components were obtained from Sakha-1 fertilized by ammonium nitrate or ammonium sulfate.…”
Section: Resultssupporting
confidence: 85%
“…In the same soil condition, Soethe et al (2013) found that urea significantly exceeded ammonium sulfate on number of branches plant -1 , dry weight plant -1 , seed index and seed yield ha -1 . Grant et al (2016) tested N fertilizers of urea and urea ammonium nitrate (UAN), as well as ammonium nitrate (AN) on flax and they reported that seed yield was higher with AN than urea. In loamy sand, Zaki et al (2018) investigate four forms of nitrogen (olive pomace 1.54% N, ammonium nitrate 33.5% N, ammonium sulfate 20.6% N and urea 46.5% N) on sugar beet, and they mentioned that ammonium nitrate and ammonium sulfate surpassed urea for most studied traits.…”
Section: Introductionmentioning
confidence: 99%
“…Weirich Neto et al (2013) studied fertilizer positioning at sowing, Lu et al (2014) worked on a planter project, and Grant et al (2016) assessed the influence of fertilizer sources on the crop installation. However, these authors did not find in the literature scientific studies examining the horizontal toothed rotor performance of planters as a function of longitudinal inclination to the metering mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Such finding, consequently, leads to a decrease of unsaturated / saturated fatty acids ratio with increasing nitrogen fertilizer rate. In this connection Grant et al (2016) reported that seed quality for flax oil tended to decline with increasing N application due to lower iodine number which revel the increase of saturated fatty acids was in account of unsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 96%